Coastal shrines and transnational maritime networks across India and Southeast Asia - Ray, Himanshu Prabha (Routledge, 2021)
Culture, the written word and the sea, 3rd century BCE to 4th century CE -- Maritime cultural landscapes and expanding networks, 4th to 7th century -- Travelling relics -- From the Tamil Coast to Vietnam : the king and the temple -- The coastal shrine and maritime networks, 7th to 13th century CE -- The Buddhist 'cosmopolis' re-examined -- Shipwrecks sites : connecting the dots -- From religious shrines to monuments : national identity to transnational heritage.